A república e o sonho The republic and its dream - Maria Tereza Chaves de Mello (Varia História, 2011)
O desencanto com a República brasileira tem sido tema de reflexões desde os seus momentos iniciais. Buscando os conteúdos concretos dos sonhos republicanos na década de 1880 e na Primeira República vamos achar uma importante defasagem entre eles não exatamente em função do marco cronológico, mas do grupo social que, respectivamente, os acalentou. The disillusion with the Brazilian Republic since its first days has been a topic of academician reflexions. Examinating the concrete contents of the 1880`s and the First Republic republican dreams we will find a substantive difference between them. To be exact, this difference must not be related to the chronological demarcation but to the social group that embraced each of them.